Still see you everywhere ebook - Gardner, Lisa (Frankie Elkin, 2024)
In this “frightening, full of twists, and completely satisfying" thriller from a New York Times bestselling author, three women: a kidnapped young girl, a serial killer on death row, and a recovering alcoholic, are on a terrifying trajectory to save a life before the clock runs out (Karin Slaughter). Missing persons expert and nomadic loner Frankie Elkin travels the country searching for the lost ones the rest of the world has forgotten.  Her specialty, cold cases that typically end in tragedy. But this one could be different. Kaylee Pierson, “The Beautiful Butcher,” confessed from the start to enticing 18 men home before slitting their throats.   As the clock winds down to her death, Pierson has finally received a lead on her baby sister, abducted years ago.  Kaylee’s dying wish: to know Leilani is safe and sound. Frankie is eager to possibly rescue a teenage girl, even if it involves flying to a remote atoll in the Pacific, where a charming tycoon is constructing an eco-resort—and possibly holding Leilani against her will. But now Frankie is trapped on an island with a dozen strangers and numerous deadly deceptions.   As the danger mounts, Frankie faces her toughest challenge with no chance of rescue, no hope of escape, and a massive storm rolling in…  “This book is a rocket.  It had me upside down and inside out.” –Gregg Hurwitz